Analisis Sebaran Tipe dan Performa Mutu Fisik Kakao pada Tiga Rentang Elevasi - Retno Utami Hatmi; Makhmudun Ainuri; Anggoro Cahyo Sukartiko (Jurnal Tanaman Industri dan Penyegar, 2018)
Cacao genotype most cultivated in Indonesia divided into three main groups, namely Criollo, Forastero, and Trinitari. Beside genetical factor, the pod and beans qualities are also strongly influenced by the environment in which the plant grows. The research aimed to analyze the types and physical qualities of the pod and bean from Patuk, Gunungkidul at three elevations range (154.00–267.20, 302.00–401.00, and 469.20–657.90 m above sea level/asl). The research was conducted at smallholder plantations in Patuk District, Gunungkidul, Yogyakarta from September until Desember 2017. As many as 40–42 samples were randomly taken from each elevation range and analyzed by descriptive statistic and one-way anova. The parameters observed  were  cocoa types identification (Criollo, Forastero, and Trinitario), pod’s physical quality (fresh weight of fruits, length to width ratio, fresh weight of beans, number of beans, and  fresh weight of one bean), and bean’s physical quality (thickness, length/width ratio, dry weight of one bean, and number of beans in 100 g). The results showed that Trinitario cacao type dominates at elevation range of 154.00–267.20 m asl, while Forastero dominates at elevation range of 302.00–401.00 and 469.20–657.90 m asl. The pod physical qualities of Criollo, Forastero, and Trinitario showed highest  fresh weight per bean at 469.20–657.90 m asl compared to those at lower elevation (increased 19.05%–31.94%). At elevation of 469.2–657.9 m asl, Forastero shown  higher beans physical quality at all variables, whereas  Criollo was significantly higher dry weight per bean and number of beans per 100 g, and Trinitario shown significantly higher bean thickness.